Special Care Optimization for Patients and Education (SCOPE): Training Pediatric Residents About Children With Special Health Care Needs - Jori Bogetz; Juia Gabhart; Caroline Rassbach; Lee Sanders; Fernando Mendoza; David Bergman; Rebecca Blankenburg (Association of American Medical Colleges, 2013)
Abstract SCOPE is a longitudinal voluntary training program that pairs a child with special health care needs (CSHCN) with a pediatric resident and faculty mentor to form a SCOPE Team. The SCOPE Team does not replace existing healthcare providers but works with them, the patient, and the family across care settings to construct the child's care to meet the patient's and family's goals. The core components of SCOPE are: (1) monthly communication with the family; (2) at least one in-person meeting with the family to complete "Toolkit" items which include a Goal Keeper to articulate goals of care, a Contact Tree for contingency planning and healthcare navigation and a Plan of Care; (3) one home visit; and (4) three one-hour meetings with SCOPE directors and mentors to discuss SCOPE cases and to reflect on the SCOPE experience. This resource provides all necessary information and materials for program implementation and execution at other institutions. Resources are available upon request from the authors for SCOPE program evaluation. SIGNIFICANCE: Successful management of pediatric illness is leading to a growing population of children with special healthcare needs (CSHCN). The Maternal and Child Health Bureau defines CSHCN as "being at increased risk for chronic physical, developmental, behavioral, or emotional conditions requiring health services beyond those needed by healthy children." Care for CSHCN is an important issue for today's healthcare system as CSHCN account for over 15% of the pediatric population and for over 70% of healthcare costs. The American Academy of Pediatrics (AAP) recommends the family-centered medical home (FCMH) and high level care coordination to improve the care for CSHCN. And yet, according to the AAP's Periodic Survey of Fellows, there continue to be significant deficiencies in the adherence to FCMH in the day-to-day care of CSHCN. In their survey, the AAP found that fewer than 50% of responding pediatricians integrate subspecialty care plans into their management of CSHCN, and fewer than 25%: (1) contact schools about a child's health and education; (2) meet with hospital discharge planning teams to assist in a child's transition back to the community; or (3) schedule time with a family to discuss the results of a visit to a subspecialist. The SCOPE program was developed to provide future pediatricians with "hands-on" training on elements of the FCMH and care coordination so vital to improving care for CSHCN. EFFECTIVENESS: SCOPE has been studied as a prospective randomized controlled trial at Lucile Packard Children's Hospital at Stanford University. SCOPE was associated with significant improvement in resident self-efficacy for patient-centered goal-setting with CSHCN. Intervention Fidelity, Feasibility and Acceptance: Over one-quarter of pediatric residents (n=22 out of 80, 27.5%) volunteered for SCOPE at Stanford University. All of intervention residents, faculty mentors and families wanted to continue participating in SCOPE after the 4-month study period. All residents responded that they would recommend SCOPE to other residents, faculty and CSHCN. In terms of the time commitment for SCOPE residents; 37.5% reported spending <1 hour/week on the program, 50% spent 1-5 hours, and 12.5% spent 6-10 hours. Overall, 70% communicated with their family at least monthly and 85% completed all Toolkit items. Primary Outcome: Learner Self-Efficacy SCOPE was associated with improvements in residents' perceived self-efficacy in caring for CSHCN. Of the nine self-efficacy items surveyed on a 5-point Likert scale, the intervention group showed statistically significant improvement in establishing patient-centered goals of care (p=0.04) compared with controls. For the intervention residents, there were statistically significant retrospective pre- and post-intervention improvements in another five out of nine self-efficacy domains including resident's ability to: (1) understand a child with special needs within the context of their own home; (2) understand how a child with special needs might impact the lives of their family; (3) create a plan of care for medically complex patients; (4) help a family navigate the healthcare system; and (5) find community resources that might benefit a child with special needs. Secondary Outcome: Patient Satisfaction All participating families wanted to continue in SCOPE at the end of the 4-month program. Although there were no statistically significant results from family data, the authors found that: 100% of families reported that their SCOPE resident understood how medical, behavioral, or other health conditions affect their child and family's day-to-day life, 57% had help with care coordination, and 100% rated their SCOPE resident as excellent when it came to "really listening to my opinions about my child's care." Generally, 25% of participating families were satisfied and 75% were very satisfied with the SCOPE program.